Commercialization of cash waqf in Negeria: An analysis of its implementation / Yusuff Jelili Amuda - Yusuff Jelili, Amuda (2016)
Cash Waqf is a viable form of Islamic endowment whose prime goal is providing relief to the less privileged citizens especially the Muslims in the society. Quite incontrovertibly, Waqf has inherent potential to ensure redistributive justice in the society given its numerous benefits. Waqf endowment provides human relief, dignity, financial support, and social needs to alleviate the struggles faced by needy Muslims such as poverty, unemployment, and lack of support. However, it is indeed ironical that despite Nigeria, an apparent Muslim dominated country, rich in both human and natural resources is still plagued by the social menace of poverty. Quite worrying is the intergenerational dimension that the incidence of the social menace of poverty is assuming in Nigeria. Educational and health problems are among other social problems confronting many Muslims in Nigeria. The rate of unemployment among the youths and adults is skyrocketing across the nation and contribute to the abject poverty. Many Muslim children, for example, are victims of exploitation, while some of them often work under unhealthy and hazardous conditions due to their parents’ inability to provide for their means of sustenance. The objective of this thesis is to examine the administration of Waqf in Nigeria from the existing legal provisions. To study the predicaments facing the Nigerian Muslims and how Islamic finance Waqf can be applied through the commercialization of cash Waqf and its implementation. In addition, it discusses how cash Waqf instrument can be used to empower lessprivileged Nigerian Muslims. It further discusses useful suggestions and solutions to the multifaceted problems facing Nigerian Muslims. The research applied qualitative and quantitative approaches to examine the applicability of commercialization of cash Waqf funds in Nigeria and its implementation. Three hundred questionnaires were distributed and collected between April and September, 2012 to Nigerian Muslims while nine iv Nigerians were selected based on expert sampling and interviewed on the commercialization of cash Waqf in Nigeria as an instrument for Nigerian Muslims empowerment. The thesis proposes strategies through which cash Waqf can be used for the creation of resources and tools for empowerment of less privilege Nigerian Muslims across the nation. The research is based on hypothesis that cash Waqf can play commendable efforts in empowering Nigerian Muslims through the lawful lucrative contract or transaction. It argues that cash Waqf can be used for educational funds, creation of employment opportunities, agriculture, and provision of tools for entrepreneurial activities. As a result, many Nigerian youths and adults would be fully empowered educationally, financially and socially. Finally, it is discovered from the findings that Waqf is viable and able to reduce poverty among less-privileged Nigerian Muslims. Similarly, there are many lucrative and profitable businesses and transactions that Waqf management can transact with cash Waqf endowment.